Nusa Penida Diving: Visit Bali Waters to See Manta Rays - Donny Juliandri Prihadi; Evi Novianti; Ahmad Ab; Ghulam Murtaza Lahbar (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
In nations with large archipelagos, marine ecotourism is becoming more popular. Ecotourism itself is a concept of tourism activities that contain elements of conservation. An integrated coastal management approach must be carried out comprehensively. This study aims to find out the challenges of marine ecotourism of special interest in Nusa Penida Bali Indonesia. The research was conducted in July 2024 using a survey method. The results showed that the challenges to marine tourism activities are getting bigger because there are so many foreign tourists who want to do diving and snorkling at Manta Point. There were 13 species of manta rays (Manta alfredi) found. Temperature is 29oC and salinity 33 ppt is ideal for Manta rays live. Management in ecotourism with manta rays must be integrated so that this achieve sustainable tourism